Defending "The Art Preservative": Class and Gender Relations in the Printing Trades Unions, 1850-1914 - Burr, Christina (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1993)
The essay explores relations of gender and class, and the strategies developed by male unionists in defence of masculine craft status in the International Typographical Union (ITU), the International Printing Pressmen's and Assistants' Union(IPP&AU), and the International Brotherhood of Bookbinders (IBB), between 1850 and 1914. The ITU and IPP&AU organized along masculine craft lines and effectively defended their status within the workplace with industrial capitalist incursions and the mechanization of the production process. A crisis to male domination of typesetting occurred with the introduction of machine typesetting in newspaper production during the early 1890s. The ITU succeeded in securing control over the operations of the machines for its predominately male membership. By the mid-19th century the work of press feeder was defined as unskilled work suitable for women and boys. With the introduction of larger and faster presses during the last two decades of the 19th century, the IPP&AU struggled to appropriate the task for masculinity using the male breadwinner ideal. The IBB actively supported the organization of women bindery workers from its inception in 1892, albeit with the intent of protecting the interests of journeymen.